Correlation of Fat Mass, Muscle Mass, and Basal Metabolic Rate with Bone Mass in Postmenopausal Women - Lubis, Leonardo; Primadhi, Raden Andri; Sitepu, Gabriel Armando (Faculty of Medicine Universitas Padjadjaran, 2025)
Background: Bone health is an important aspect of aging, particularly in postmenopausal women who experience estrogen deficiency that increases the risk of osteoporosis and related complications. Although components of body composition have individually been associated with bone health, their relative contributions remain incompletely understood. This study aimed to examine the correlations of fat mass, muscle mass, and basal metabolic rate (BMR) with bone mass in postmenopausal women.Methods: A cross-sectional analytic study was conducted in March 2025 using data from 40 postmenopausal women obtained from the Bandung Sport and Health Nabati Nutrition (B-SHENN) Project. Spearman’s rho correlations analysis was used to assess relationships between fat mass, muscle mass, BMR and bone mass. Multiple linear regression analysis was performed to identify the most influential predictor of bone mass.Results: Fat mass, muscle mass, and BMR were all significantly and positively correlated with bone mass (p<0.001). Among these variables, muscle mass showed the strongest correlation with bone mass (r=0.991). Multiple linear regression analysis demonstrated that muscle mass was the only independent predictor significantly associated with bone mass (B=0.069; p=0.022).Conclusions: Fat mass, muscle mass, and BMR are associated with bone mass in postmenopausal women, with muscle mass emerging as the strongest predictor. These findings underscore the importance of maintaining or increasing muscle mass as a key modifiable factor in strategies to preserve bone health and reduce osteoporosis risk in postmenopausal women.